Interplay Between Connexin40 and Nitric Oxide Signaling During Hypertension. Issue 4 (April 2015) - Le Gal, Loïc; Alonso, Florian; Mazzolai, Lucia; Meda, Paolo; Haefliger, Jacques-Antoine
Abstract : Connexins (Cxs) and endothelial nitric oxide synthase (eNOS) contribute to the adaptation of endothelial and smooth muscle cells to hemodynamic changes. To decipher the in vivo interplay between these proteins, we studied Cx40-null mice, a model of renin-dependent hypertension which displays an altered endothelium-dependent relaxation of the aorta because of reduced eNOS levels. These mice, which were either untreated or subjected to the 1-kidney, 1-clip (1K1C) procedure, a model of volume-dependent hypertension, were compared with control mice submitted to either the 1K1C or the 2-kidney, 1-clip (2K1C) procedure, a model of renin-dependent hypertension. All operated mice became hypertensive and featured hypertrophy and altered Cx expression of the aorta. The combination of volume- and renin-dependent hypertension in Cx40−/− 1K1C mice raised blood pressure and cardiac weight index. Under these conditions, all aortas showed increased levels of Cx40 in endothelial cells and of both Cx37 and Cx45 in smooth muscle cells. In the wild-type 1K1C mice, the interactions between Cx40 and Cx37 with eNOS were enhanced, resulting in increased NO release. The Cx40–eNOS interaction could not be observed in mice lacking Cx40, which also featured decreased levels of eNOS. In these animals, the volume overload caused by the 1K1C procedure resulted in increased phosphorylation of eNOS and in a higher NO release. The findings provide evidence that Cx40 and Cx37 play an in vivo role in the regulation of eNOS. Abstract : Supplemental Digital Content is available in the text.